The Network Is Your Customer - DAVID L. ROGERS (Yale University Press, 2011)
as we fi nd it harder to make the time for it). A book offers a unique opportunity to explore an idea in depth and vet a hypothesis in meticulous detail to see how it holds up after the initial thrill of a bold discovery has worn off. It offers the challenge of tying many ideas together and teasing out the complexities of their relationships to one another. The biggest challenge in writing a book like this is that you are writing for the future. The fi rst words you commit to the page will likely be read by your average reader two or more years later. This forces you to step back from the news of the moment, the trends of the day, and take a much broader view of your subject. Technology is changing too fast for me to write about it here in an up-to-the-minute fashion. (As I write this, my latest speeches already contain new cases that are too recent to make it in the book.) This forced me to focus not on technology but on the underlying behaviors that shape our adoption of technology and give it impact and meaning. By understanding our behaviors, as individuals linked and living together in the seamless web of our digital networks, I hope to shed some light on the opportunities that lie ahead for us all.